Armed [videorecording (DVD)] - Van Peebles, Mario; Fichtner, William; Guzman, Ryan, 1987-; Barrera, Shakira (Sony Pictures Home Entertainment, 2018)
Chief is a former US marshal who has fallen on hard times after he led his team of undercover agents on a raid that went horribly wrong. As Chief struggles to get his life back on track a former colleague reappears in his life and explains that all of the survivors from his unit are suffering the same symptoms he is and that there may be a larger conspiracy at hand.